A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
y = 3x + 4
2x + 3y = 10
Which of the following steps could be used to solve by substitution?
3x + 4 = 2x + 3y
2x + 3(3x + 4) = 10
2(3x + 4) + 3y = 10
3(y = 3x + 4)
anonymous
 one year ago
y = 3x + 4 2x + 3y = 10 Which of the following steps could be used to solve by substitution? 3x + 4 = 2x + 3y 2x + 3(3x + 4) = 10 2(3x + 4) + 3y = 10 3(y = 3x + 4)

This Question is Closed

jim_thompson5910
 one year ago
Best ResponseYou've already chosen the best response.1Hint: \[ \Large {\color{red}{y}} = 3x+4\\ \Large 2x + 3{\color{red}{y}} = 10 \]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0@jim_thompson5910 i dont get the hint..

jim_thompson5910
 one year ago
Best ResponseYou've already chosen the best response.1the two 'y's are the same, so you can replace the 3y in the second equation with 3(...) the dot dot dot is whatever y is equivalent to

jim_thompson5910
 one year ago
Best ResponseYou've already chosen the best response.1example \[ \Large \color{red}{y} = x+2\\ \Large 5x + 10\color{red}{y} = 17 \] After substitution, we get \[ \Large 5x + 10\color{red}{y} = 17\\ \Large 5x + 10(\color{red}{y}) = 17\\ \Large 5x + 10(\color{red}{x+2}) = 17 \]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0@jim_thompson5910 could you possibly tell me what you got so i can see how you got it

jim_thompson5910
 one year ago
Best ResponseYou've already chosen the best response.1do you see in my example how I replaced y with x+2 ?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0@jim_thompson5910 i suck @ math and this my last answer on my homework

jim_thompson5910
 one year ago
Best ResponseYou've already chosen the best response.1all you're doing is replacing y with what it is equivalent to. Look back at my example again

jim_thompson5910
 one year ago
Best ResponseYou've already chosen the best response.1In my example, y is equivalent to x+2 so that's how I replaced the y with x+2 in the second equation. Don't forget the parenthesis

Study_together
 one year ago
Best ResponseYou've already chosen the best response.0It's B because \[2x+3(3x+4)=10\]can be substituted to \[5x+7=10\]and this is the substitution property.

marihelenh
 one year ago
Best ResponseYou've already chosen the best response.0The first equation shows what y is equal to. \[y=3x+4\] So, in the second equation, you can put what the y was equal to in the place of where the y was. \[2x+3y=10\] \[2x+3(3x+4)=10\]
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.